Development of Green Chemistry-Based Pratical Guidebook for Chemistry Education in Senior High School - Mawaddah Nasution; Lelya Hilda, Lelya; Nur Azizah Putri Hasibuan (Orbital: Jurnal Pendidikan Kimia, 2025)
This study aims to develop valid, practical, and effective green chemistry-based chemistry laboratory instructions to support chemistry learning at Muarasipongi 1 Public High School. The method used is Research and Development (R&D) with a 4D model limited to the Develop stage due to time constraints. The research subjects consisted of 23 students in class XI-1 with purposive sampling technique. The research object was a green chemistry-based chemistry practicum manual. The research instruments included expert validation sheets (material, media, and language), practicality questionnaires, and learning outcome tests. Data analysis using descriptive quantitative analysis to assess the validity, practicality, and effectiveness of the product through percentages, N-Gain, and student responses. The results of expert validation showed that the product was highly valid, with an average percentage of 87.5%. Practicality tests conducted by teachers and students showed that the product was highly practical, with percentages of 89% and 91%, respectively. Effectiveness tests based on student learning outcomes and scientific attitudes showed a percentage of 68% and were classified as highly effective. These practical guidelines integrate green chemistry principles, such as waste prevention and the use of safe materials. Thus, this product is suitable for use as a support for environmentally friendly and contextual chemistry learning at the senior high school level.